PENDIDIKAN SEPANJANG HAYAT MENURUT PERSPEKTIF ISLAM (KAJIAN TAFSIR TARBAWI) - Intan Caroline; Arin Khairunnisa (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to describe lifelong education according to an Islamic perspective. The method used in this research is a literature review with tarbawi interpretation studies. The focus of this research is lifelong education according to an Islamic perspective, which is broken down into threesubfocus, namely 1 lifelong education according to the Qur'an 2 lifelong education according to the hadith and 3 lifelong education according to the scholars. Based on the results of the research and discussion it can be concluded that Islam requires its people to seek knowledge, both for men and women, from birth to death Islam provides strong motivation for its followers to seek knowledge in the form of virtue (high degrees), great rewards, and other conveniences. in fact, in Islam the degree of a scientist (ulama) is more important than an official, a wealthy person, and a worshiper.